Potential anti-cancer features of metformin - Puła, Aleksandra; Krzysiek, Urszula; Podgórska, Klaudia; Gorczyca, Kamila; Artykiewicz, Klaudia; Słupczyńska, Aleksandra; Urbaś, Weronika; Czarkowski, Marcin; Kozieł, Paweł; Grodkiewicz, Maria (Journal of Education, Health and Sport, 2022)
INTRODUCTION AND PURPOSE: Metformin is one of the most frequently prescribed medications in the whole world. This lipophilic biguanide is widely used as a first-line medicine for patients suffering from type 2 diabetes mellitus because of its high effectiveness in monotherapy, and in connection with other antidiabetic drugs. Glucose-lowering properties of metformin were initially used only in the therapy of type 2 diabetes mellitus, but some data indicate that these properties might state an alternative in the prevention or treatment of some cancers both among diabetic and non-diabetic patients. STATE OF KNOWLEDGE: Metformin molecular mechanisms of action were thoroughly investigated, differentiated, and described, but in the context of the glucose-lowering effect. As a multiway drug, used mainly in diseases characterized by an increased level of glucose in the blood, numerous medical trials were conducted to find other treating properties of metformin. Recently, a few reports presented the potential connection between using metformin in the prevention and treatment of neoplasms in the same mechanisms. The scientists analyzed the influence of metformin’s action on various cancers and drew conclusions. The research on potential anti-cancer features of metformin was conducted for a relatively short period and still presents a challenge to scientists. CONCLUSIONS: The aim of this review is to gather current knowledge and present the latest discoveries about potential anti-cancer features of metformin. We discuss the potential underlying molecular mechanisms of metformin’s action in the human body and indicate the connection between the prevention and treatment of neoplasms. Additionally, we point out the exact cancers in which metformin might play a significant role.